Iogurte caprino adicionado de prebiótico e geleia de manga: aspectos físico-químicos, microbiológicos e sensoriais - Alves, Layane Maciel (2015)
The increasing search for healthy foods enables the development of products that provide benefits to consumer health. This study aimed to elaborate goat yogurt added prebiotic and mango jam, combining the therapeutic benefits and nutritional value of goat milk yogurt and mango to the functional properties of inulin. Inulin is a dietary fiber widely used in food both for its technological attributes as for its nutritional benefits. For product development, was used an experimental design type Rotational central composite design composed of eleven trials. By Response Surface Methodology (RSM), three goat yogurt formulations were selected with different concentrations of inulin and gelatin, taking as dependent variable the apparent viscosity parameter. The selected goat yogurt formulations (A: 3 % inulin and 0.5 % gelatin; B: 5 % of inulin and 0.45 % gelatin and C: 7 % inulin and 0.4 % gelatin), mango jam and raw materials (goat milk and mango) were submitted to physical, chemical and physico-chemical evaluations. The goat yogurt added prebiotic and mango jam were submitted to microbiological analyzes (count of fecal coliforms, molds and yeasts, total lactic acid bacteria, coagulase-positive staphylococci and Salmonella spp. determination) and sensory evaluation (acceptance tests, with respect to the attributes: appearance, color, aroma, flavor, texture and overall impression, using hedonic scale of 9 points; preference and purchase attitude tests). The results of all analyzes receive statistical treatment through the Analysis of Variance (ANOVA) and the means were compared using the Tukey test. According to the results, it was found that all manufactured products attended the required legal specifications. The sensory evaluation showed that the three formulations were well accepted for all attributes, with no significant difference (p>0,05) in the acceptance and preference of the samples, except for appearance. The three samples showed positive intention to purchase by potential consumers. The addition of different concentrations of inulin and gelatin allowed to obtain goat yogurt with similar consistency to bovine products found in the market. Therefore, this study enabled the development of a technological alternative to using raw materials produced in the Northeast region of Brazil, goat milk and mango, and the making available of an innovative dairy product in the market.